2016
DOI: 10.1111/evo.12903
|View full text |Cite
|
Sign up to set email alerts
|

Environmental constraints and call evolution in torrent-dwelling frogs

Abstract: Although acoustic signals are important for communication in many taxa, signal propagation is affected by environmental properties. Strong environmental constraints should drive call evolution, favoring signals with greater transmission distance and content integrity in a given calling habitat. Yet, few empirical studies have verified this prediction, possibly due to a shortcoming in habitat characterization, which is often too broad. Here we assess the potential impact of environmental constraints on the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 114 publications
0
60
0
Order By: Relevance
“…The high frequency parameters may be related with their tendency to vocalize in close proximity to mountain cascade streams, which would create a low-frequency background noise (Preininger et al 2007). It was shown that low background noise may induce frogs to call at higher frequency rates than expected from their body size, thereby improving the signal-to-noise ratio of their calls (Penna et al 2005, Wells 2007, Goutte et al 2016). Our study also recorded that the values of some temporal call parameters of Ophryophryne elfina sp.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency parameters may be related with their tendency to vocalize in close proximity to mountain cascade streams, which would create a low-frequency background noise (Preininger et al 2007). It was shown that low background noise may induce frogs to call at higher frequency rates than expected from their body size, thereby improving the signal-to-noise ratio of their calls (Penna et al 2005, Wells 2007, Goutte et al 2016). Our study also recorded that the values of some temporal call parameters of Ophryophryne elfina sp.…”
Section: Discussionmentioning
confidence: 99%
“…This method complements the historical approach of ancestral state reconstruction used on the same data set in Goutte et al . (). Goutte et al .…”
Section: Introductionmentioning
confidence: 97%
“…Torrent‐breeding ranids generally produce shorter and higher‐pitched advertisement calls than other closely related frogs (Arch et al ., ; Boonman & Kurniati, ; Goutte et al ., ), although there appears to be no single typical advertisement call type for torrent‐breeding frogs. Investigating habitat characteristics at a finer scale, Goutte et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations